EL ESPACIO EN LA NARRATIVA - Reyes Tarazona, Roberto (2010)
The paper presents considerations about the meaning of space in literary fiction, taking as its starting point the essential elements of human activities: time and space. Develop approaches to literary theory and criticism, made by various authors, about how that space is integrated into the narrative form and is expressed in it. It then turns to the subject of space and narrative in Peru stressing the narrative production from the second half of the twentieth century, with particular emphasis on the city.